SERVICE QUALITY MODEL ON PASSENGER SATISFACTION AT SULTAN HASANUDDIN MAKASSAR INTERNATIONAL AIRPORT - MULYADI NUR; FATMAWATI SABUR (Jurnal Vokasi Keteknikan, 2023)
Vocational education is a process of introducing practical subjects to the world of work through industrial visits, providing vocational guidance and providing applied teaching and training to people who need work. We use the term vocationalization which includes the meaning of vocationalization. Introduction to practical subjects in the world of work includes the development of vocational competencies, personality competencies, social competencies, soft skills, work skills, technical skills, vocational careers, salary systems, work systems, work safety, employment regulations and legislation and so on. Based on this, the research study aims to determine 1) The influence of check-in counter facilities on passenger satisfaction at Sultan Hasanuddin Makassar international airport. 2) The influence of Avsec facilities on passenger satisfaction at Sultan Hasanuddin Makassar international airport. The research method used is survey research with a quantitative approach. The results of this research indicate that there is an influence of service quality on passenger satisfaction at Sultan Hasanuddin Makassar International Airport. The test results show that tcount is greater than ttable. Service quality has a joint influence on the five variables tested on passenger satisfaction. The test results show that Fcount is greater than Ftable. So this research hypothesis is accepted.